Efectos de un programa de pausas activas sobre la percepción de desórdenes músculo-esqueléticos en trabajadores de la Universidad de Antioquia (2011)
ABSTRACT: This study established the effects of a program of Active Breaks (AB) in musculoskeletal disorders (MSD), in workers of the University of Antioquia, A quantitative, quasi-experimental design was applied; groups were intervened at frequencies of 2, 3 and 4 times a week, for a period of 10 minutes each. The initial sample was 343 people and a final 187 people. The Standarized Nordic Questionnaire for MSD was applied, along with a survey. In the past 12 months, most of the population had MSD in 3 or 4 body segments such as neck, lower back, upper back and wrist. Applying the intragroups Student’s T, statistically significant p<0.05 values were found. I.e. the Abs decreased the MSDs in relation to the problems of the last year and over the last 7 days. Some groups did not differ statistically significant, regarding difficulties and doctor visits because of MSD.